Maternal and Neonatal Outcomes in Pregnant Patients with Pre-Existing Cardiac Diseases - Rahman, Fahd Ur; Saif, Mohsin; Khan, Ismail Ahmed; Siddique, Muhammad Bilal; Yousaf, Husnain; Alam, Waqas; Safi, Shoaib Iqbal; Khan, Aleena; Samore, Naseer Ahmed; Azad, Naseem (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the maternal and fetal outcome in pregnant patients with preexisting cardiac conditions and to determine the prevalence of different cardiac diseases among pregnant patients.Study Design: This was across sectional study.Place and Duration of Study: Tertiary Cardiac Care Center in Rawalpindi Pakistan, from Dec 2021 to Apr 2022.Methodology: This was across sectional study done in a tertiary cardiac care center in Rawalpindi. A total of (n=100) pregnant patients with pre-existing cardiac diseases were included in the study from Dec 2021 to Apr 2022 over a period of 5 months. Prospective data including patients' demographics and their outcomes was collected using preformed proformas. Data was analyzed by SPSS version-23. Prevalence of maternal death, fetal death, maternal complications and neonatal complications were the primary outcomes of study. Descriptive statistics were run to present categorical data in frequencies and percentages. Chi-square and Fisher Exact Test was applied to find the association between study variables at 95% CI and 5% margin of error (α=5%).Results: A total of (n=100) patients were included in our study which was conducted from Dec 2021 to Apr 2022. Maternal mortality was observed in 6% (n=6) of patients. Maternal outcomes of pulmonary edema were seen in 24% (n=24) of patients and post-partum hemorrhage was seen in 14% (n=14) patients. Three parameters of perinatal outcome were studied i.e., low birth weight, preterm delivery and death. 39% (n=39) neonates were found to have low birth weight, 22% (n=22) were preterm and perinatal mortality was 21% (n=21). The primary results of our study showed 6% (n=6) maternal mortality and 21% (n=21) perinatal mortality.Conclusion: Overall maternal mortality was 6% while perinatal mortality was 21%. There existed a statistically significant (p